2009
DOI: 10.1111/igc.0b013e3181a3cc94
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 2-(18F) Fluoro-2-Deoxy-d-Glucose Positron Emission Tomography/Computed Tomography on Recurrent Ovarian Cancer Diagnosis and on Selection of Patients for Secondary Cytoreductive Surgery

Abstract: The objective of this prospective study was to compare the sensitivities and the specificities of combined 2-(F) fluoro-2-deoxy-D-glucose positron emission tomography/computed tomography (PET/CT), abdominal/transvaginal ultrasound (US), and CT for diagnosing recurrent ovarian cancer (OC) and to evaluate the influence of PET/CT on referral of patients with solitary recurrence to secondary cytoreductive surgery. From April 2005 to November 2007, 60 patients were consecutively included to PET/CT 68 times. The inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 26 publications
5
17
0
1
Order By: Relevance
“…In detecting recurrent ovarian cancer, FDG-PET/CT had a sensitivity of 85-97% and a specificity of 90-100% and was higher than those of ultrasonography and CT [64], although negative predictive value is low (42.9%) because of the high rate of false-negative findings for micro or cystic lesions [65]. FDG-PET/CT modified the diagnostic or treatment plan, by leading to the use of previously unplanned therapeutic procedures in 57.9% of patients and the avoidance of previously planned diagnostic procedures in 42.1% of patients [66].…”
Section: Response Evaluation Surveillance and The Management Of Recmentioning
confidence: 86%
See 1 more Smart Citation
“…In detecting recurrent ovarian cancer, FDG-PET/CT had a sensitivity of 85-97% and a specificity of 90-100% and was higher than those of ultrasonography and CT [64], although negative predictive value is low (42.9%) because of the high rate of false-negative findings for micro or cystic lesions [65]. FDG-PET/CT modified the diagnostic or treatment plan, by leading to the use of previously unplanned therapeutic procedures in 57.9% of patients and the avoidance of previously planned diagnostic procedures in 42.1% of patients [66].…”
Section: Response Evaluation Surveillance and The Management Of Recmentioning
confidence: 86%
“…To date no adequate evidence has been provided by a large scale or prospective study partly because of rareness of uterine sarcoma. In cervical cancer, radiotracers other than FDG such as 64 Cu-labeled diacetylbis(N4-methylthiosemicarbazone) ( 64 Cu-ATSM) were used to demonstrate hypoxia and 11 C-choline for proliferative activity, yet have not gained popularity [14].…”
Section: Pet Radiotracermentioning
confidence: 99%
“…Conversely, our data show that a significant difference in PFS and OS is confirmed also for later follow-up. 18 F-FDG PET/CT performed for identifying recurrences during the restaging process in patients with ovarian cancer was previously reported to have good sensitivity (85-97 %) and specificity (90-100 %), superior to CT [24], although with a low NPV (42.9 %) due to the high rate of falsenegative findings for microlesions or cystic lesions [25]. Recently, Chen et al [26] reported that, in 152 patients with ovarian cancer, the NPV of 18 F-FDG PET/CT was 93.9 %, reaching 100 % in those subjects who underwent PET/CT during follow-up, for the increase of CA125 but negative or indeterminate imaging findings and for the suspicion of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…FDG PET/BT'nin rekürren hastalık saptamada tek başına BT'ye göre tanısal duyarlılığı ve pozitif prediktif değeri oldukça yüksektir. PET ayrıca tümör belirteç yüksekliğinin standart görüntüleme yöntemleri ile açıklanamadığı hasta gruplarında nüks odağının lokalizasyonunda yüksek tanısal doğruluk göstermekte olup (120), önemli oranda hasta grubunda tedavi planının belirlenmesinde etkilidir.…”
Section: Pelvikmalignitelervepet/mr Jinekolojikmalignitelerdepet/mrunclassified